Perfil clínico-laboratorial dos casos de dengue hemorrágica e dengue com complicação internados no Hospital Universitário João de Barros Barreto, no período de 2003 a 2008 - ZUCATELLI, Carlos Alberto Ferrete (2023)
Dengue is an acute viral disease booming worldwide, being then a serious public health problem. The clinical presentation forms include asymptomatic infection, classic disease, hemorrhagic fever and unusual ways. This study aimed to describe the clinical and laboratory profile of patients with Dengue Hemorrhagic Fever (DHF) and Dengue with Complication (DC) at the Hospital João de Barros Barreto (period 2003 to 2008) through the collection of information obtained from medical records of patients and statistical analysis support under the program BioEstat version 5. DC was the most common form of disease (n = 68, 66.67%) among 102 individuals included in study. DHF was most frequent among children (n = 21, 61.76%), while the group of young adults predominated in the DC (n = 31, 45.58%). The signs and symptoms most found in both groups were fever, headache, myalgia and spontaneous bleeding. The group with DHF showed up hemoconcentration (high hematocrit) and increased occurrence of cavities spills at the time of admission. Thrombocytopenia below 50,000 mm³ and bleeding were common in both groups. All cases of death occurred in the DC. This study shows that cases of more severity with fatal outcome are involved with complications other than leakage and bleeding, highlighting the importance of unusual forms as cause of death.